Silk-Based Biocompatible Random Lasing - Caixeiro,S; Gaio,M; Marelli,B; Omenetto,FG; Sapienza,R (Advanced Optical Materials, 2016)
Biocompatible silk random lasing is obtained by nanostructuring silk proteins into a disordered porous matrix via a self-assembly technique. Lasing action is revealed by spectral narrowing and threshold behavior, and it is sensitive to pH variations in the aqueous environment. Silk random lasing provides a versatile biocompatible system, opening up opportunities for biophotonic applications and biosensing.